2021
DOI: 10.1177/21649561211002461
|View full text |Cite
|
Sign up to set email alerts
|

Online Mindfulness May Target Psychological Distress and Mental Health during COVID-19

Abstract: Background The COVID-19 pandemic has dramatically affected mental health, creating an urgent need for convenient and safe interventions to improve well-being. Online mindfulness interventions show promise for improving depression, anxiety, and general well-being. Objective To assess: 1) the impact of online mindfulness on psychological distress, 2) altruistic efforts, and 3) the quantity, quality, and availability of online mindfulness resources during the COVID-19 pandemic. Methods 233 participants (203 U.S.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The number of interventional studies that investigated the impact of mindfulness practices on individuals’ mental health during the COVID-19 pandemic is limited; nevertheless, they have reported promising results. Almost all the reviewed studies were congruently reported that, after participating in mindfulness interventions, the participants’ mental health and well-being improved (Lim et al 2021 ; Zhang et al 2021 ; Weis et al 2021 ; Matiz et al 2020 ; Farris et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of interventional studies that investigated the impact of mindfulness practices on individuals’ mental health during the COVID-19 pandemic is limited; nevertheless, they have reported promising results. Almost all the reviewed studies were congruently reported that, after participating in mindfulness interventions, the participants’ mental health and well-being improved (Lim et al 2021 ; Zhang et al 2021 ; Weis et al 2021 ; Matiz et al 2020 ; Farris et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversano et al found that mindfulness was the best predictor of psychological distress (Conversano et al, 2020 ). Online mindfulness sessions also help to reduce anxiety, stress, and concern about the COVID‐19 (Farris et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown in young adults of U.S. that greater levels of resilience are capable of attenuating the negative effect of their stress levels [ 24 ]. Even the online mindfulness session helped the participants decrease momentary anxiety, stress and COVID-19 concern [ 11 ]. Taken together, our study finds out that that when it comes to dealing with pressures, resilience is crucial and meditation interventions help achieve that resilience levels.…”
Section: Resultsmentioning
confidence: 99%